2016
DOI: 10.1371/journal.pone.0149639
|View full text |Cite
|
Sign up to set email alerts
|

Role of UBIAD1 in Intracellular Cholesterol Metabolism and Vascular Cell Calcification

et al.

Abstract: Vascular calcification is an important risk factor associated with mortality among patients with chronic kidney disease. Intracellular cholesterol metabolism is involved in the process of vascular cell calcification. In this study, we investigated the role of UbiA prenyltransferase domain containing 1 (UBIAD1) in intracellular cholesterol metabolism and vascular cell calcification, and identified its subcellular location. Primary human umbilical vein smooth muscle cells (HUVSMCs) were incubated with either gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 36 publications
1
9
1
Order By: Relevance
“…UBIAD1 inhibits post-ubiquitination steps in ERAD of reductase (12), the molecular basis of which is currently under investigation. In contrast to our findings summarized above, previous studies reported reduced levels of cholesterol not only in cells overexpressing wild-type, full-length UBIAD1, but also in those expressing truncated and SCD-associated variants (including N102S) of UBIAD1 (22)(23)(24). In addition, a mild accumulation of intracellular cholesterol was observed upon RNAi-mediated knockdown of UBIAD1.…”
Section: Ubiad1 Coordinates Sterol and Nonsterol Isoprenoid Synthesiscontrasting
confidence: 99%
“…UBIAD1 inhibits post-ubiquitination steps in ERAD of reductase (12), the molecular basis of which is currently under investigation. In contrast to our findings summarized above, previous studies reported reduced levels of cholesterol not only in cells overexpressing wild-type, full-length UBIAD1, but also in those expressing truncated and SCD-associated variants (including N102S) of UBIAD1 (22)(23)(24). In addition, a mild accumulation of intracellular cholesterol was observed upon RNAi-mediated knockdown of UBIAD1.…”
Section: Ubiad1 Coordinates Sterol and Nonsterol Isoprenoid Synthesiscontrasting
confidence: 99%
“…4B). This finding agrees with a recent paper by Liu et al [45] describing that knock-down of UBIAD1, a nonmitochondrial prenyltransferase that synthesizes CoQ in the Golgi, induces an increase in intracellular cholesterol amount. Moreover, Suárez-Rivero et al [46] reported that in fibroblasts from familial hypercholesterolemia patients, the mevalonate pathway was dysregulated, resulting in increased cholesterol levels and CoQ deficiency.…”
Section: Discussionsupporting
confidence: 93%
“…This finding agrees with a recent paper by Liu et al . [45] describing that knock‐down of UBIAD1, a nonmitochondrial prenyltransferase that synthesizes CoQ in the Golgi, induces an increase in intracellular cholesterol amount. Moreover, Suárez‐Rivero et al .…”
Section: Discussionmentioning
confidence: 99%
“…These encompass (i) synthesis of human endogenous form of vitamin K 2 (MK-4) from derivates of a plant form vitamin K 1 [ 10 , 20 25 ], (ii) prevention of oxidative damage in tissues by synthesis of non-mitochondrial coenzyme Q10 [ 26 , 27 ], and (iii) direct and indirect interaction with proteins that regulate cholesterol synthesis and transport (HMGCR, SOAT1, apoE) [ 10 , 28 , 29 ]. UBIAD1 protein plays a crucial role in maintaining lipid-cholesterol homeostasis in different cell types [ 10 , 12 , 21 , 30 , 31 ] but the molecular mechanism by which UBIAD1 pathogenic variants affect the cornea leading to lipid deposition in SCD patients has yet to be determined.…”
Section: Discussionmentioning
confidence: 99%